2000
DOI: 10.1177/0306624x00442002
|View full text |Cite
|
Sign up to set email alerts
|

A Trauma-Focused Individual Therapy Approach for Adolescents with Conduct Disorder

Abstract: Trauma is proposed as a key to understanding the development and persistence of conduct disorder in conjunction with other contributing factors. Trauma history is virtually universal in this population, and trauma effects can help to account for many features of the disorder including lack of empathy, impulsivity, anger, acting out, and resistance to treatment. The current standard of care fails to fully address trauma, which may partially explain the low success rate. A trauma-focused individual therapy appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 56 publications
0
10
0
1
Order By: Relevance
“…Following positive case reports of MASTR with two incarcerated youth (Greenwald, 2000), an open trial found that all six adolescents treated with MASTR showed reduced trauma symptoms, reduced presenting problem behaviors, and improved school performance (Greenwald, 2002a). Given the difficulty in treating adolescents with CPs and the likely value of addressing their trauma-related issues, the authors believed that the potential value of MASTR and the encouraging outcomes from the open trial indicated that further study was warranted.…”
Section: Emdr and Mastr Treatmentsmentioning
confidence: 99%
“…Following positive case reports of MASTR with two incarcerated youth (Greenwald, 2000), an open trial found that all six adolescents treated with MASTR showed reduced trauma symptoms, reduced presenting problem behaviors, and improved school performance (Greenwald, 2002a). Given the difficulty in treating adolescents with CPs and the likely value of addressing their trauma-related issues, the authors believed that the potential value of MASTR and the encouraging outcomes from the open trial indicated that further study was warranted.…”
Section: Emdr and Mastr Treatmentsmentioning
confidence: 99%
“…On the one hand, they suggest that some researchers will adopt a trauma-focused approach in their studies meaning that for these researchers -the critical factor is direct exposure to the violence and destruction of war-the types of potentially traumatic exposure typically assessed by war-events checklists (Miller & Rasmussen, 2010). Trauma-focused clinical treatments are generally individualized (Greenwald, 2000), though group interventions are also possible. On the other hand, groups of researchers explore and promote psycho-social approaches that is -focused primarily on the stressful social and material conditions caused or worsened by armed conflict‖ including poverty, malnutrition, displacement, and destruction of social networks (Miller & Rasmussen, 2010).…”
Section: War-induced Migrationmentioning
confidence: 99%
“…"dopalacze" 4 przez dzieci i młodzież 5 . Tylko w lipcu 2015 roku całą Polskę obiegła informacja o masowych zatruciach dopalaczami wśród osób dorosłych, ale i 15-latków, do których doszło 4 "Dopalacze" -czyli nowe narkotyki -to produkty o zróżnicowanym składzie, które łączy jedna wspólna cecha: zawierają substancje psychoaktywne, które wpływają na układ nerwowy człowieka w podobny sposób jak dotychczas znane narkotyki.…”
Section: Rodzaje Czynów Karalnych Wśród Nieletnichunclassified